CURRÍCULOS E PEDAGOGIAS DAS MANIFESTAÇÕES DO PÚBLICO DO FUTEBOL DE MULHERES EM HASHTAGS NO TWITTER/X. - ALINI SILVA PEIXOTO (2025)
This research is characterized as an exploratory field study with a qualitative approach. The objective is to analyze the curricula and pedagogies related to the production of knowledge and power in the public manifestations of the hashtags on Twitter/X associated with the Campeonato Brasileiro Feminino Neoenergia 2023. More specifically, this dissertation aimed to identify and contextualize the curricula and their aspects and how they are presented in the discourses inserted in the platform; to analyze the power relations in the discourses present in the hashtags; to apprehend displacements about concepts such as gender, woman, masculine/feminine and to perceive how Women's Soccer is permeated by these relations and (re)significations. The analyses were carried out from the perspective of Cultural Studies focusing on power relations, agencies, and resistances in the curricula and pedagogies that are presented from the discourses found in the hashtags linked to the competition. Aspects of the curriculum related to the valorization of practice were identified, considering both the effective success and the process of the teams during the competition. An interesting fact was the organization of the fans in specific hashtags and the relationship of interaction of the public in the form of comments/responses to the posts that used the hashtags. Furthermore, it was observed the disputes that were established in the discourses over the meanings related to the representations of football played by women, as well as the players themselves. Discourses inserted in power games that contest or validate the practice of these women were perceived, as well as the use of discursive strategies based on a certain form of verbal violence to invalidate their soccer. An agency movement exercised by the clubs was also identified in relation to the dissemination and availability of live broadcasts of matches that were not televised by Rede Globo and/or SporTV, holders of the broadcasting rights. Other aspects were related to the presence of masculinities curricula inferring meanings to the representations related to soccer as practice and curricula of invisibility disputing meanings with the curricula of valorization of women's soccer. The curricular constructions present in the hashtags allowed the delineation of a Pedagogy of Occupation of Spaces, due to the pedagogical strategies used to put into combat, in the power games, the meanings that the shared representations disputed in this context of Twitter/X.